Liberal Intergovernmentalism and Its Critics*. (30th August 2018) - Kleine, Mareike; Pollack, Mark
Abstract: This introduction sets the stage for a special issue devoted to evaluating the contribution and continued relevance of Liberal Intergovernmentalism (LI) – a theory first formulated 25 years ago in this journal – in today's politicized and crisis‐ridden European Union (EU). We review the debates prompted by LI's three core claims about national preference formation, intergovernmental bargaining and institutional choice, as well as by the theory's three policy‐relevant corollaries relating to the EU's democratic deficit, its constitutional settlement and its role in the world. Liberal intergovernmentalism, we argue, remains highly relevant in today's EU, offering important insights and serving to structure much of the academic debate about the prospects of the Union in a time of crisis. Nevertheless, a revitalized LI faces the dual challenges of theorizing both the causes and consequences of mass politicization of EU politics, as well as the prospect of endogenous change in the direction of greater integration or disintegration.